Model pedagogi genre untuk mengembangkan keterampilan membaca pemahaman bahasa indonesia di sekolah dasar - Pitaloka, Deby; Istiyati, Siti; Yulisetiani, Septi (Universitas Sebelas Maret, 2023)
This study aims to describe of genre pedagogy learning model on Indonesian language comprehension in elementary school. This research uses literature study method with descriptive analysis technique. In this study, researchers sought data from the number or relevant books on genre pedagogy learning model and reading comprehension in Indonesian language in elementary school. Genre pedagogy is a text-based learning model based on a teaching and learning cycle where teachers provide guidance and interaction to learners before learners create texts independently. In practice, this genre pedagogy is implemented using four stages, namely the initial stage of Building Knowledge, the second stage is modelling, the third stage is joint construction and the last stage, namely independent construction. The application of the genre pedagogy model can indirectly motivate learners to utilize various learning resources around them in reading comprehension, especially when learners build their own understanding.